PERAN GURU BK DALAM MENINGKATKAN KOMUNIKASI ANTARPRIBADI PESERTA DIDIK DI SMPN 14 PADANG - Purnama, Sari - (Bimbingan dan Konseling, 2014)
This research is motivated by concerns about the role of teachers in improving interpersonal comunication guidance and conseling learnerson the ground, that the teachers role has not been implemented to the maksimum guidance and conseling because there are students who donât ask and when asked they donât answer. While counselor have the time, while only guidanceand counseling. counselor have only hourâs time to provide information. This study aimed to describe 1) the role of counselor in improving student understanding of interpersonal comunication 2) the role of teachers in improving interpersonal comunication effective. This research is descriptive quqntitqtive. The population in this study all students in the SMPN 14 Padang champign totaiy 378 people. The tecnique used is stratified random sampling in deffrend class. So the tatal sampel of 41 people. The instrument used in this study was a questionnaire. While the persentage of data analisis tecniques used. The result of this study revelialed that:1) The role of counselor in improving the understanding of learners categorized excellent interpersonal comunication. 2) the role of counselor improving interpersonal comunication effective is very good. Based on the result of the study, the researchers suggested further enhance counselor the role in improving interpersonal communication.